Soviet Law: The Problem of Its Succession - Vladimir Valentinovich Kozhevnikov (Britain International for Academic Research (BIAR-Publisher), 2022)
This article is devoted to the problems of continuity of Soviet law on the first ethanes of its development. Despite the denial of the continuity of Soviet law by some scholars, the opposite is proved by referring to specific legal acts.